Senegal : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency; and Securities Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Senegal's financial sector is dominated by 10 commercial banks, which account for more than 85 percent of total financial sector assets. The banking system in the country has gradually regained health and is generally well regulated and supervised. The high concentration of credit risk in bank loan portfolios is unavoidable given that banks have little scope for further portfolio diversification. Microfinance development in the country has kept pace with the dynamic evolution of this sector in the West African Economic and Monetary Union region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet